Bolt wire rod and parts with improved delayed fracture resistance and manufacturing method thereof
By optimizing the alloy composition and manufacturing process of Mn-B steel wire rods to form residual austenite at the martensite lath boundary, the delayed fracture resistance of high-strength bolts is substantially enhanced, addressing the hydrogen trapping issues associated with existing materials.
Patent Information
- Application Number
- JP2023537383
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-18
- Filing Date
- 2021-12-14
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2041-12-14
AI Technical Summary
High-strength bolt materials face challenges in resisting delayed fracture due to hydrogen trapping at grain boundaries and lath boundaries, which is exacerbated by alloying elements like Mn that cause structure imbalances during heat treatment.
The development of Mn-B steel wire rods with a specific alloy composition (C: 0.15-0.30%, Si: 0.05-0.35%, Mn: 0.95-1.35%, P: 0.030% or less, S: 0.030% or less, Ti: 0.005-0.030%, B: 0.0010-0.0040%) and a manufacturing process that includes finishing rolling and winding within specific temperature ranges, followed by austenitization, quenching, and tempering, to form residual austenite at the martensite lath boundary, thereby slowing hydrogen diffusion.
This approach significantly improves the delayed fracture resistance of high-strength bolts by creating a microstructure that effectively traps hydrogen, preventing crack initiation and propagation.
Smart Images

Figure 0007660200000003 
Figure 0007660200000001 
Figure 0007660200000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a wire rod and a part that can be used for fastening bolts in automobiles and structures, and a method for manufacturing the same, and more particularly to a wire rod and a part for bolts having improved delayed fracture resistance, and a method for manufacturing the same. [Background technology]
[0002] Wire rods used as materials for fastening bolts in automobiles and structures are required to have higher strength as automobiles become lighter and structures become smaller. Generally, the strength of steel is increased by utilizing the strengthening mechanisms of metals, such as cold working, grain refinement, martensite strengthening, and precipitation strengthening.
[0003] However, the cold working, grain boundaries, martensite lath boundaries, and fine precipitate boundaries that are used as strengthening mechanisms act as hydrogen traps in the steel and also act as causes of delayed fracture. For these reasons, there is a problem of delayed fracture in high-strength bolts with a tensile strength of 1 GPa or more.
[0004] To solve these problems, conventionally, Cr-Mo alloy steel with Mo added was used for bolt steel of 1 GPa or more having a tempered martensite structure, but there were attempts to replace Cr-Mo steel with Cr-B steel to meet the need for cost reduction due to the development of bolt manufacturing process technology. As a result, cost reduction was realized by using Cr-B steel for bolts used in structures that do not have a significant impact on safety, and after confirming its safety, Cr-B steel is also being used for some fastening bolts in automobiles.
[0005] In the automotive industry, there is a need to develop bolt materials that can be even more cost-effective than Cr-B steel in order to reduce costs to the utmost.To meet this need, technological development has been carried out recently to apply Mn-B steel, which utilizes Mn, which is cheaper than Cr, to high-strength bolt materials of 1 GPa or more.
[0006] However, Mn has a higher alloy element segregation than Cr during the continuous casting manufacturing process of steel, which causes deviations even during the same bolt heat treatment process. There is also a technical problem that delayed fracture resistance deteriorates due to the microstructural imbalance that occurs during the heat treatment process, making it difficult to apply Mn-B steel to high-strength bolts of 1 GPa or more. Summary of the Invention [Problem to be solved by the invention]
[0007] The object of the present invention is to provide a wire rod for high strength bolts, a bolt and a manufacturing method thereof, which are capable of reducing costs and have improved delayed fracture resistance by controlling the microstructure of Mn-B steel through the alloy composition and manufacturing method. [Means for solving the problem]
[0008] The wire rod for bolts of the present invention with improved delayed fracture resistance is characterized by containing, by weight%, C: 0.15 to 0.30%, Si: 0.05 to 0.35%, Mn: 0.95 to 1.35%, P: 0.030% or less, S: 0.030% or less, Ti: 0.005 to 0.030%, B: 0.0010 to 0.0040%, and the balance being Fe and unavoidable impurities.
[0009] Furthermore, the bolt part of the present invention with improved delayed fracture resistance is characterized by containing, by weight%, C: 0.15 to 0.30%, Si: 0.05 to 0.35%, Mn: 0.95 to 1.35%, P: 0.030% or less, S: 0.030% or less, Ti: 0.005 to 0.030%, B: 0.0010 to 0.0040%, with the balance being Fe and unavoidable impurities, and containing, by volume fraction, 0.3 to 2.0% retained austenite and the remainder being a tempered martensite structure.
[0010] Further, the method for producing a wire rod for bolts having improved delayed fracture resistance of the present invention is characterized by comprising a step of finish rolling a steel material containing, by weight%, 0.15 to 0.30% C, 0.05 to 0.35% Si, 0.95 to 1.35% Mn, 0.030% or less P, 0.030% or less S, 0.005 to 0.030% Ti, 0.0010 to 0.0040% B, with the balance being Fe and unavoidable impurities, in a temperature range of 880 to 980°C, and a step of coiling the steel material in a temperature range of 830 to 930°C.
[0011] In addition, the manufacturing method of the present invention for a bolt part having improved delayed fracture resistance is characterized by including a step of forming a high-strength bolt wire rod having improved delayed fracture resistance into a part, an austenitizing step of heating in a temperature range of 870 to 940°C, a quenching step in a temperature range of 50 to 80°C, and a tempering step in a temperature range of 400 to 600°C to obtain a part. Effect of the Invention
[0012] According to the present invention, the high strength bolt component having improved delayed fracture resistance of the present invention can improve delayed fracture resistance by forming retained austenite at martensite lath boundaries and delaying hydrogen diffusion inside the steel material. [Brief description of the drawings]
[0013] [Figure 1] 1 is a transmission electron microscope (TEM) photograph showing the fraction and thickness of retained austenite in Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] This specification does not describe all elements of the embodiments, and content that is common in the technical field to which the present invention belongs or that is overlapping between the embodiments will be omitted.
[0015] Furthermore, when any part is said to "comprise" a certain component, this does not mean to exclude other components, but rather that it can further include other components, unless specifically stated to the contrary.
[0016] The singular expression includes the plural expression unless there is a clear exception in the context.
[0017] The present invention will be described in detail below.
[0018] In the present invention, the inventors discovered that it is possible to ensure delayed fracture resistance in Mn-B steel, which has relatively poor delayed fracture resistance due to structural imbalance caused by Mn segregation, by utilizing a retained austenite structure with a slow hydrogen diffusion rate, and thus completed the present invention.
[0019] Retained austenite is formed at lath-to-lath boundaries where mechanically stable austenite does not transform into martensite lath. The retained austenite formed at the martensite lath boundaries has a face-centered cubic (FCC) structure, and hydrogen diffusion speed is about 10,000 times slower than tempered martensite structure with a body-centered cubic (BCC) or body-centered tetragonal (BCT) structure. Therefore, when hydrogen that has flowed into steel meets the retained austenite, the diffusion speed is slowed down, and delayed fracture resistance can be improved.
[0020] A wire rod for high strength bolts with improved delayed fracture resistance according to one embodiment of the present invention contains, by weight%, C: 0.15-0.30%, Si: 0.05-0.35%, Mn: 0.95-1.35%, P: 0.030% or less, S: 0.030% or less, Ti: 0.005-0.030%, B: 0.0010-0.0040%, and the balance being Fe and unavoidable impurities.
[0021] The reasons for limiting the numerical values of the alloying element contents in the embodiments of the present invention will be described below. In the following, unless otherwise specified, the unit is % by weight.
[0022] The carbon (C) content is 0.15 to 0.30%. C is an element added to ensure the strength of the product. If the carbon content is less than 0.15%, it is difficult to ensure the target strength in the present invention, and if it exceeds 0.30%, it can hinder the formation of retained austenite, which has excellent mechanical stabilization and is formed by hydrostatic pressure at the lath martensite boundary during quenching. In addition, if the C content is high, the lath becomes thick and the thickness of the retained austenite also becomes thick, so that the thickened retained austenite can act as a trap part that captures hydrogen and can deteriorate delayed fracture. Therefore, in the present invention, the C content is limited to 0.15 to 0.30%.
[0023] The silicon (Si) content is 0.05 to 0.35%. Silicon is not only useful for deoxidizing steel, but also an effective element for ensuring strength through solid solution strengthening. If the silicon content is less than 0.05%, the strength of the steel is insufficient through deoxidation and solid solution strengthening, and if it exceeds 0.35%, delayed fracture resistance may deteriorate due to deterioration of impact properties. Therefore, in the present invention, the silicon content is limited to 0.05 to 0.35%.
[0024] The manganese (Mn) content is 0.95 to 1.35%. Mn is an element that improves hardenability, and is a very useful element that forms a substitutional solid solution in the matrix structure and exerts a solid solution strengthening effect. If the Mn content is less than 0.95%, the above-mentioned solid solution strengthening effect and hardenability are insufficient, making it difficult to ensure the strength targeted in the present invention, and if it exceeds 1.35%, segregation can induce deviations in heat treatment performance between products. Therefore, in the present invention, the Mn content is limited to 0.95 to 1.35%.
[0025] The phosphorus (P) content is 0.030% or less (0% is excluded). P is an element that segregates at grain boundaries to reduce toughness and delayed fracture resistance, and therefore, in the present invention, the upper limit of P is set to 0.030%.
[0026] The sulfur (S) content is 0.030% or less (0% is excluded). Like P, S is an element that not only segregates at grain boundaries to reduce toughness, but also forms low-melting-point sulfides and inhibits hot rolling. Therefore, in the present invention, the upper limit of S is limited to 0.030%.
[0027] The titanium (Ti) content is 0.005 to 0.030%. Ti is an element that combines with N flowing into the steel to form titanium carbonitrides and prevents B from combining with N. If the Ti content is less than 0.005%, it is insufficient to form titanium carbonitrides from N flowing into the steelmaking process, making it difficult to utilize the above-mentioned effect of B, and if it exceeds 0.030%, coarse carbonitrides are formed, which can deteriorate delayed fracture resistance. Therefore, in the present invention, the Ti content is limited to 0.005 to 0.030%.
[0028] The boron (B) content is 0.0010 to 0.0040%. B is an element that improves hardenability. If the B content is less than 0.0010%, it is difficult to expect the aforementioned effect of improving hardenability. If the B content exceeds 0.0040%, Fe is present at the grain boundaries. 23It forms (CB)6 carbides, which induces embrittlement of the austenite grain boundaries and deteriorates delayed fracture resistance. Therefore, in the present invention, the B content is limited to 0.0010 to 0.0040%.
[0029] The balance other than the alloy composition is Fe. The bolt wire rod having improved delayed fracture resistance of the present invention may contain other impurities that may be normally contained in the industrial production process of steel. Since such impurities are known to anyone having ordinary knowledge in the technical field to which the present invention pertains, the present invention does not particularly limit the type and content of the impurities.
[0030] A high strength bolt component with improved delayed fracture resistance according to one embodiment of the present invention contains, by weight%, 0.15 to 0.3% C, 0.05 to 0.35% Si, 0.95 to 1.35% Mn, 0.030% or less P, 0.030% or less S, 0.005 to 0.03% Ti, 0.001 to 0.004% B, with the balance being Fe and unavoidable impurities, and contains, by volume fraction, 0.3 to 2.0% retained austenite and the remainder being tempered martensite.
[0031] If the fraction of the retained austenite structure is less than 0.3%, it is difficult to expect it to act as an obstacle to retard hydrogen diffusion. If it exceeds 2.0%, the retained austenite is formed thickly not only at lath boundaries but also at austenite grain boundaries, making it difficult to retard hydrogen diffusion, and this can reduce the effect of improving delayed fracture resistance.
[0032] In addition, the retained austenite in the high strength bolt component according to the present invention is formed at the martensite lath boundary and can have a thickness of 100 nm or less. If the thickness of the retained austenite exceeds 100 nm, the retained austenite acts as a trap for accumulating hydrogen and can act as a starting point for hydrogen-induced delayed fracture cracks. Therefore, in the present invention, it is preferable to control the thickness of the retained austenite to 100 nm or less.
[0033] Next, a method for producing a wire rod for a high strength bolt and a part having improved delayed fracture resistance according to an embodiment of the present invention will be described.
[0034] The wire rod for high strength bolts and parts having improved delayed fracture resistance according to the present invention may be manufactured by various methods, and the manufacturing method is not particularly limited. However, as one embodiment, the wire rod for high strength bolts and parts having improved delayed fracture resistance may be manufactured by the following method.
[0035] The wire rod for high strength bolts according to the present invention, which has improved delayed fracture resistance, includes a step of finish rolling a steel material containing, by weight%, 0.15-0.3% C, 0.05-0.35% Si, 0.95-1.35% Mn, 0.030% or less P, 0.030% or less S, 0.005-0.030% Ti, 0.001-0.004% B, with the balance being Fe and unavoidable impurities, in a temperature range of 880-980°C, and a step of coiling the steel material in a temperature range of 830-930°C.
[0036] First, a steel material satisfying the above-mentioned alloy composition is prepared and finish-rolled at a temperature of 880 to 980° C. The rolled wire material is then wound into a coil shape at a temperature of 830 to 930° C.
[0037] In this case, if the wire rod rolling temperature is less than 880°C or the coiling temperature is less than 830°C, the surface layer is in a quasi-two-phase region, so a surface ferrite decarburized layer can be formed by phase transformation, and a ferrite decarburized layer can also be formed on the surface during heat treatment of the bolt, deteriorating delayed fracture resistance. In addition, if the wire rod finish rolling temperature exceeds 980°C or the coiling temperature exceeds 930°C, decarburization is accelerated by diffusion, and a ferrite decarburized layer can be formed on the surface.
[0038] The coiled wire may then be drawn, spheroidized, heat treated, coated and bolt formed as desired.
[0039] The wrought wire can then be austenitized, hardened and tempered to produce the final bolt component.
[0040] A method for manufacturing a bolt part according to one embodiment of the present invention includes an austenitizing step of heating the processed wire rod in a temperature range of 870 to 940°C, a quenching step in a temperature range of 50 to 80°C, and a tempering step in a temperature range of 400 to 600°C to obtain a bolt part.
[0041] In this case, the austenitizing heat treatment can be performed in the temperature range of 870 to 940°C. If the heat treatment temperature is less than 870°C, the austenite reverse transformation does not occur sufficiently, so that the martensite structure is formed non-uniformly after quenching, and the toughness may be deteriorated. If the heat treatment temperature exceeds 940°C, the austenite grain size becomes coarse, the martensite lath is formed stably with a long length during quenching, and the retained austenite is formed at the lath boundary in a shape smaller than the target shape in the present invention.
[0042] Also, the quenching step may be performed at a temperature range of 50 to 80° C. If the temperature of the quenching coolant is less than 50° C., fine quenching cracks may occur in the threads of the bolt due to thermal deformation, which may lead to delayed fracture, whereas if the temperature exceeds 80° C., sufficient quenching is not performed, and in addition to the mechanically stable retained austenite in the laths, retained austenite is formed at the prior austenite grain boundaries, which acts as a hydrogen trapping site and may lead to delayed fracture.
[0043] In addition, the tempering step may be performed at a temperature range of 400 to 600°C, and strength and toughness may be imparted according to the use and purpose of the final product. If the tempering temperature is less than 400°C, embrittlement may occur, and if it exceeds 600°C, it is difficult to realize the strength intended in the present invention.
[0044] The high strength bolt component with improved delayed fracture resistance produced by the present invention contains a microstructure containing, by volume fraction, 0.3 to 2.0% retained austenite and the remainder tempered martensite structure.
[0045] In a high strength bolt component with improved delayed fracture resistance according to one embodiment of the present invention, retained austenite is formed at martensite lath boundaries and has a thickness of 100 nm or less.
[0046] The present invention will be described in detail below with reference to examples.
[0047] Working Example The delayed fracture resistance of the cold heading (CHQ) parts of the examples and comparative examples was evaluated by a delayed fracture simulation in which the wire was manufactured into the final bolt, the bolt was fastened to a structure with a fastening force of the yield strength, and then the bolt was immersed in a 5% hydrochloric acid + 95% distilled water solution for 10 minutes, and the presence or absence of cracks in the threads, which are the stress concentration areas, was observed.
[0048] The volume fraction and thickness of the retained austenite in the microstructure of the bolt parts were measured by measuring the average volume fraction and maximum thickness of five images taken with a transmission electron microscope (TEM). When using the X-ray diffraction (XRD) method, retained austenite with a low fraction of 2.0% or less cannot be observed, so the retained austenite was observed using a transmission electron microscope.
[0049] Wires of Examples 1 to 9 and Comparative Examples 1 to 7, which satisfy the alloy compositions in Table 1 below, were produced under the production conditions according to the present invention to obtain final test bolts.
[0050] Specifically, the wire was finish-rolled at 880-980°C, then wound into a coil shape at 830-930°C, the wound wire was austenitized at 870-940°C, and then quenched in a refrigerant at 50-80°C. In order to ensure a tensile strength of 1050±12MPa, the wire was tempered at a temperature of 400-600°C to obtain the final bolt test specimens.
[0051] [Table 1]
[0052] In the invention examples 1 to 9, the fraction and thickness of the retained austenite (γ) satisfied the conditions of the present invention of 0.3 to 2.0% of the retained austenite fraction and 100 nm or less of the retained austenite fraction, and no delayed fracture cracks were generated. In the comparative example 1, the C content was 0.14%, which did not satisfy the lower limit of 0.15% of C proposed in the present invention, so that the retained austenite was not formed and did not act as a hydrogen diffusion barrier, resulting in delayed fracture cracks.
[0053] In Comparative Example 2, the C content was 0.32%, which exceeded the upper limit of 0.30% proposed in the present invention, and the thickness of the retained austenite exceeded 100 nm. The retained austenite exceeding 100 nm actually acted as a trap that captured hydrogen, inducing delayed fracture cracks.
[0054] In Comparative Example 3, the Si content was 0.44%, which exceeded the upper limit of 0.35% of Si proposed in the present invention, and induced delayed fracture cracks.
[0055] In Comparative Example 4, the Mn content was 0.85%, which is below the lower limit of 0.95% proposed in the present invention. As a result, sufficient hardening was not performed and retained austenite was not formed, which resulted in delayed fracture.
[0056] In Comparative Example 5, the Mn content was 1.40%, exceeding the upper limit of 1.35% proposed in the present invention, and the residual austenite fraction was high, resulting in delayed fracture cracks. In Comparative Example 5, the thickness of the residual austenite satisfied the thickness of the residual austenite of 100 nm or less proposed in the present invention, but the residual austenite fraction was 2.2%, exceeding the upper limit of 2.0% proposed in the present invention, and it was derived that when the bolt was tightened at yield strength, transformation induced martensite was formed, resulting in deterioration of delayed fracture resistance.
[0057] In Comparative Example 6, the P content was 0.031%, which exceeded the upper limit of 0.030% proposed in the present invention. P segregated at the prior austenite grain boundaries, degrading the bond energy of the grain boundaries and causing delayed fracture cracks.
[0058] In Comparative Example 7, the B content was 0.0004%, which is lower than the lower limit of 0.001% proposed in the present invention. As a result, sufficient quenching was not performed, and residual austenite was formed at less than 0.3%, resulting in delayed fracture.
[0059] Next, Invention Example 3 and Comparative Examples 8-1 to 8-4, which satisfy the alloy composition of Invention Example 3 in Table 1 according to the present invention, were manufactured under the manufacturing conditions shown in Table 2 below to obtain final bolt test pieces.
[0060] [Table 2]
[0061] Inventive Example 3, which satisfied the finish rolling temperature, coiling temperature, and austenitizing temperature according to the present invention, the residual austenite fraction and thickness proposed in the present invention were satisfied, and no delayed fracture cracks occurred. FIG. 1 is a transmission electron microscope (TEM) photograph showing the fraction and thickness of the residual austenite in Inventive Example 3, and from FIG. 1, it was confirmed that in Inventive Example 3 manufactured according to the present invention, residual austenite was formed at the martensite lath boundary. In Comparative Example 8-1, the finish rolling temperature exceeded 980°C, the upper limit proposed in the present invention, and the coiling temperature also exceeded 930°C, the upper limit, so that the prior austenite grain size in the wire rod became coarse compared to the prior austenite grain size in the final bolt, and the residual austenite fraction did not reach 0.3%, resulting in delayed fracture.
[0062] In Comparative Example 8-2, the finish rolling temperature did not reach 880°C, which is the lower limit proposed in the present invention, and the coiling temperature also did not reach 830°C, which is the lower limit. As a result, the prior austenite grain size in the wire rod became smaller than that of the final bolt, the retained austenite fraction exceeded 2.0%, and delayed fracture occurred.
[0063] In Comparative Example 8-3, the austenitizing heat treatment temperature was 950°C, which is higher than the upper limit of 940°C proposed in the present invention. As a result, the prior austenite grain size of the final bolt was increased, and the residual austenite fraction was formed at less than 0.3%, resulting in delayed fracture.
[0064] In Comparative Example 8-4, the austenitizing heat treatment temperature was 860°C, which is lower than the lower limit of 870°C proposed in the present invention. As a result, the prior austenite grain size of the final bolt was reduced, the retained austenite fraction exceeded 2.0%, and delayed fracture occurred.
[0065] Although exemplary embodiments of the present invention have been described above, the present invention is not limited thereto, and a person having ordinary knowledge in the art will understand that various modifications and variations are possible within the scope of the concept and scope of the claims set forth below.
Claims
1. The steel comprises, by weight percent, C: 0.15-0.30%, Si: 0.05-0.35%, Mn: 0.95-1.35%, P: 0.030% or less, S: 0.030% or less, Ti: 0.005-0.030%, B: 0.0010-0.0040%, and the balance being Fe and unavoidable impurities; The steel has a volume fraction of 0.3 to 2.0% retained austenite and the remainder of a tempered martensite structure. The retained austenite is formed at martensite lath boundaries; A high-strength bolt component having improved delayed fracture resistance, characterized in that the component has a thickness of 100 nm or less.
2. A step of forming the high strength bolt wire rod having improved delayed fracture resistance into a part; an austenitizing step of heating in the temperature range of 870-940°C; quenching at a temperature in the range of 50 to 80°C; and tempering the resulting product at a temperature in the range of 400 to 600°C to obtain a high strength bolt component. The high strength bolt part comprises: The steel has a volume fraction of 0.3 to 2.0% retained austenite and the remainder of a tempered martensite structure. The retained austenite is formed at martensite lath boundaries; The thickness is 100 nm or less, The high strength bolt wire rod is A step of finish rolling a steel material containing, by weight%, C: 0.15 to 0.3%, Si: 0.05 to 0.35%, Mn: 0.95 to 1.35%, P: 0.030% or less, S: 0.030% or less, Ti: 0.005 to 0.030%, B: 0.0010 to 0.0040%, with the balance being Fe and unavoidable impurities, in a temperature range of 880 to 980°C; and winding the bolt at a temperature in the range of 830 to 930° C.
Citation Information
Patent Citations
High strength bolt steel excellent in delayed fracture resistance, and bolt
JP1998036940A
B-containing steel excellent in cold workability and delayed fracture resistance, its production and bolt
JP1999293401A
High-strength wire rod to be induction-hardened superior in cold workability and impact resistance, and steel component using the wire rod
JP2005133152A